Sediment transport capacity of concentrated flows on steep loessial slope with erodible beds - Hai Xiao (Scientific Reports, 2017)
Abstract Previous research on sediment transport capacity has been inadequate and incomplete in describing the detachment and transport process of concentrated flows on slope farmlands during rill development. An indoor concentrated flow scouring experiment was carried out on steep loessial soil slope with erodible bed to investigate the sediment transport capacity under different flow rates and slope gradients. The results indicated that the sediment transport capacity increases with increasing flow rate and slope gradient, and these relationships can be described by power functions and exponential functions, respectively. Multivariate, nonlinear regression analysis showed that sediment transport capacity was more sensitive to slope gradient than to flow rate, and it was more sensitive to unit discharge per unit width than to slope gradient for sediment transport capacity in this study. When similar soil was used, the results were similar to those of previous research conducted under both erodible and non-erodible bed conditions. However, the equation derived from previous research under non-erodible bed conditions with for river bed sand tends to overestimate sediment transport capacity in our experiment.